2018
DOI: 10.1007/s10973-018-7524-0
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic (IR, Raman, UV–Vis) study and thermal analysis of 3d-metal complexes with 4-imidazolecarboxylic acid

Abstract: In this work, the spectroscopic (IR, Raman, UV-Vis) and thermal properties of 3d metal complexes with 4-imidazolecarboxylic acid were studied in order to determine the effect of 3d metals [i.e., Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II)] on the electronic structure and physicochemical properties of the ligand. The spectroscopic studies showed that the 3d-transition metals stabilize the electronic system of 4-imidazolecarboxylic acid. Similar results were obtained previously for benzoic and pyridinecarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…IR, NMR studies and literature X-ray data on the structure of dacarbazine complexes [36] showed that metals such as copper and cobalt coordinate the ligand (dacarbazine) through the carbonyl group and the nitrogen atom from the imidazole ring. A similar type of metalligand coordination has been observed for 3d-transition metal complexes with imidazole carboxylic acid [38]. On the basis of spectroscopic studies (IR, Raman) and theoretical calculations, it was found that 3d metals affect the electronic charge distribution of the aromatic ring of ligand.…”
Section: Nmr Spectrasupporting
confidence: 63%
See 1 more Smart Citation
“…IR, NMR studies and literature X-ray data on the structure of dacarbazine complexes [36] showed that metals such as copper and cobalt coordinate the ligand (dacarbazine) through the carbonyl group and the nitrogen atom from the imidazole ring. A similar type of metalligand coordination has been observed for 3d-transition metal complexes with imidazole carboxylic acid [38]. On the basis of spectroscopic studies (IR, Raman) and theoretical calculations, it was found that 3d metals affect the electronic charge distribution of the aromatic ring of ligand.…”
Section: Nmr Spectrasupporting
confidence: 63%
“…The total electronic density of the C-ring of the copper complex is greater than that of the cobalt complex. Studies of 4imidazole carboxylic acid complexes with 3d-transition metals (including copper and cobalt) also showed that copper and cobalt had a stabilizing effect on the aromatic system of the imidazole ring [38].…”
Section: Nmr Spectramentioning
confidence: 99%
“…41 The presence of the characteristic bands at 1072 cm −1 for 1, 1018 cm −1 for 2, 1083 cm −1 for 3 suggest the v C–N stretching vibrations of the imidazole ring. 42 The absorptions about 650–880 cm −1 of 1–3 can be attributed to the v C–H bending vibrations of phenyl ring.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the CSAP and SSAP exhibit peaks at 1584 cm −1 and 1386 cm −1 due to the carboxylate (COO − ) ion generated by neutralization of the carboxyl groups. Since carboxylate has a resonance structure, the C=O stretching vibrations are divided into symmetrical and asymmetrical peaks [ 27 ]. The band at 1690 cm −1 in the spectrum of OS is assigned to the stretching vibrations of the carbonyl groups due to oxidation of the starch molecule.…”
Section: Resultsmentioning
confidence: 99%